Pengaruh Pendidikan Pencegahan Kekerasan Seksual Berbasis Animasi terhadap Pengetahuan dan Sikap Remaja - Muharomah, Lulu Lutpia; Darmawati, Irma; Wahyoe Puspita, Asih Purwandari (UI Scholars Hub, 2025)
Background. Sexual violence is a major problem that impacts the physical and psychological health of adolescents. Prevention efforts are needed through health education that is in accordance with the characteristics of adolescents. Animation media is considered effective because it can convey messages audio-visually and attractively. Purpose. This study aims to assess the influence of Animation-Based Education on adolescents' knowledge and attitudes regarding the prevention of sexual violence. Method. The study used a one-group pretest–posttest design with 59 student respondents in Cimahi City. The intervention was in the form of an educational animated video on sexual violence prevention of ±5 minutes four times in two weeks. Knowledge of sexual violence prevention was measured using the Child Knowledge of Abuse Questionnaire (CKAQ) and attitudes were measured using the Sexual Violence Attitudes questionnaire from Ambiya. Univariate and bivariate analysis used the Wilcoxon Signed Rank Test for variable knowledge and the Paired Sample t-test for attitude variable. Results. The results showed a significant improvement in adolescents' knowledge and attitudes after being given the intervention (p<0.00). The majority of respondents showed improved knowledge and a positive attitude after the intervention.